Determinants of Female Labour Force Participation in Pakistan - Naheed, Sobia; Waseem, Muhammad; Bashir, Arshed; Saeed, Rashed; Mahmood, M. Ather (Pakistan Journal of Humanities and Social Sciences, 2024)
Women's labour force affects the household economy as well as economic growth. Women's labour force contribution rate is also increasing gradually in Pakistan. We attempted to determine the determinants and impact of women's labour force contribution on households. Time series data were taken from World Bank and WDI from 1981 to 2020. Based on the unit root test the ARDL model was finalized. Akaike Information Criterion (AIC) was used to verify the significance of the estimated ARDL-VECM model. There was a positive and negative association among selected variables. Variables such as female population, ratio of female workers, female headed households and female literacy rate positively and significantly impacted the female labour force participation whereas fertility rate and child mortality rate negatively but significantly determined the participation of females in labour force. Based on findings, government should focus on health and education sectors with special focus on females in order to provide reasonable educational and health facilities in order to support females participation in various economic activities of the country.